Academic and pastoral teams working in partnership to support distance learning students according to curriculum area. Issue 1 (1st January 2019) - Hilliam, Rachel; Williams, Gareth
ABSTRACT: The Open University has provided distance learning opportunities for 50 years and succeeds in offering its students many of the attributes of flexible learning. This article is a case study of the development of a highly successful partnership model of academic and pastoral support in mathematics and statistics at The Open University, and its application to flexible learning. The model involved reciprocal governance structures and equal status in the making of curriculum-related decisions. The model is illustrated by three examples throughout the student learning journey before, during and after study. The partnership model is applicable regardless of the curriculum area; hence the article is relevant to all disciplines. Equally, although the model was developed in the context of distance learning, its ethos remains relevant in the face-to-face context, all the more so given the prevalence of flexible learning and the growing number of distance learning courses being offered at traditional Higher Education Institutions across the sector. Abbreviations: OU: Open University; School: School of Mathematics and Statistics; SST: Student Support Team; VLE: Virtual Learning Environment